Hemodynamic status and autonomic regulation under VVI pacing - SAKAI, A.; TERADA, Y.; IJIMA, H.; MINATO, N.; MAETA, H.; OKAMURA, K.; HORI, M.; FUKUDA, I.; FUJITA, T.; TSUTSUI, T.; MITSUI, T. (Jinko Zoki, 1985)
Under VVI pacing, effects on the cardiovascular system of rising from the supine to the sitting position were studied in three patients with pacemaker syndrome as compared in four control patients. In individuals with pacemaker syndrome, sudden sitting brought a fall in blood pressure and right atnal pressure, a decrease in atrial rate and %FS. In control group, pharmacological denervation disclosed the same hemodynamic changes as shown in pacemaker syndrome. A genesis of pacemaker syndrome was most likely due to autonomic insufficiency associated with diminished responses to baroreceptor stimulation.